Assessing the impact of solar trolleys on farm household income in Punjab Pakistan - Ali Sher; Saman Mazhar; Dil Bahadur Rahut; Ali Azam; Muhammad Arif Watto; Hongping Yuan (Scientific Reports)
Abstract This study explores the determinants of solar trolley adoption and its impact on farm and non-farm earnings using a cross-sectional dataset of 617 farm households from Punjab, Pakistan. We develop two models – a logit model and a Heckman two-stage model – to overcome potential endogeneity and selection bias. Interestingly, we find significant variations in solar energy utilization among farmers across the given scenarios – layman, efficient, and entrepreneurial – with those in the latter scenario achieving the shortest pay-off time of 1.72 years. Moreover, solar trolleys substantially enhance the productivity of intensively irrigated cereals, resulting in economic benefits of USD 193.80 and USD 134.90 per acre for rice and hybrid maize, respectively. Our analysis reveals that factors such as access to solar subsidy, solar information, smartphone ownership, livestock and tractor ownership, and groundwater table depth positively influence solar trolley adoption. The Heckman model demonstrates that access to solar trolley increases the likelihood of engaging in non-farm activities, with solar trolley ownership and access to solar subsidies contributing to non-farm income by 37.8% and 17.2%, respectively. After controlling for various characteristics at the farm, individual, and village levels, participation in self-help groups, access to skill development programs, proximity to towns, and paved roads were found to be factors that promote non-farm entrepreneurship in rural areas. These findings offer valuable insights for policymakers aiming to promote agricultural solarization and enhance rural household livelihood options, food security, income, and resilience in wake of climate change. Agricultural policies focusing on agricultural solarization should provide the necessary amenities to facilitate entrepreneurship to achieve multiple sustainable development goals in rural and remote areas.